Efficient Matrices for Evaluating the Performance of IEEE 802.16 based Mesh Network at Node Level - kumar, Deepak; Gangwar, R.C. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Wimax stands for World Wide Interoperatability for Microwave Access. This technology is based on the IEEE 802.16 standard (also called as Broad band Wireless Access). Wimax is a telecommunication technology that provides wireless transmission of data in different transmission modes from Point-to-Point, Point-to-Multipoint providing the 75 mb/s broadband speed without the need of cables. Different Routing Protocols have been used in wireless network. This paper presented an analysis on those routing protocols especially designed for wireless networks. A study and comparison on the performance of three routing protocols (AODV, DSR, and DSDV) for Mobile WiMAX environment is done. The performance matrix includes Packet Delivery fraction (PDF), Throughput, End to End Delay, and number of packet dropped were identified. The study used OPNET 14 simulator for the comparison on the performance analysis. Successfully results found that AODV protocol outperform the DSR and DSDV.